Modelagem da evapotranspiração máxima para as culturas do pimentão e do tomateiro em estufa plástica na primavera - Tazzo, Ivonete Fátima (2008)
Growing crops in protected environment aiming to increase productivity and quality of vegetables is commonly used in Southern Brazil , mainly to reduce the seasonality of production caused by a winter cold season. Sweet pepper is an alternative profitable crop to rotate with other crops inside greenhouse, because of their adaptation and tomato is the most cultivated crop in these environments in Brazil . The cultivation during the Spring inside plastic greenhouses is used to take advantage of a previous area and structure already assembled, as most growers are small farmers. Moreover, an important advantage is the quality and earliness of crops grown in these environments. In order to achieve these goals and reach the potential yield, water demand has to be met through irrigation. An inadequate irrigation, both surplus and shortage, may not only decrease yield, but also may lead to diseases and leaching of ions, mainly nitrates. Aiming to develop, test and evaluate regression models to calculate maximum evapotranspiration based upon meteorological and crop variables for sweet pepper (Capsicum annuum L) and tomato (Lycopersicon esculentum, Mill) grown in plastic greenhouse during the Spring, an experiment was conducted during the Spring of the 2005 and during of the 2006, in a plastic greenhouse in the Crop Production Department of the Federal University of Santa Maria. Maximum evapotranspiration (ETm) of sweet pepper and tomato was determined with three drainage lysimeters filled with substrate for each crop. The ETm (in mm) was obtained from the difference between irrigated and drained water. Regression models to estimate the ETm were generated using the experimental data measured during the Spring of 2005, being selected only those with the slope parameters significant by the t test (p <0.05) and with coefficient of determination (R2) greater than 0.60. The performance of the selected models was evaluated using the experimental data collected during the Spring 2006. Statistics used for models evaluation were: mean square root error (RMSE), coefficient of determination (R2), coefficient of correlation (r), coefficient of accuracy or agreement (d) and coefficient of confidence (c) and models were ranked based upon the coefficient of confidence and the "sum of the values of the ordinary positions" of all the statistics (åPO). Results showed that leaf area index and plant height are the crop variables that result in the best performance of the model to estimate ETm of sweet pepper and tomato grown in greenhouses during the Spring. Models that consider Etm divided by the root square of leaf area index showed good performance, although in their generation they were not always the best ones. Air vapor pressure deficit and incoming solar radiation measured inside greenhouses, and air vapor pressure deficit, incoming solar radiation, net radiation and reference evapotranspiration measured outside the greenhouse, are the meteorological variables that presented the best ETm estimation for sweet pepper and tomato grown in plastic greenhouse during the spring.